Analisis Pengelolaan Sampah Rumah Tangga di Kecamatan Tuah Madani Kota Pekanbaru (Studi Kasus) - Ansori, Putra Budi (Sekolah Tinggi Ilmu Ekonomi Riau, 2024)
This research was conducted in three housing complex locations, namely Perum Griya Cemara Asri, Forestry Vocational School Housing Complex, Perum Kampung Dalam Lestari in Pekanbaru City. The aim of this research is: to determine the pattern and role of the community in managing waste and identify waste management problems in three housing locations in Tuah Madani sub-district. This research is qualitative research with a descriptive approach. This research directly describes the phenomenon of waste management in three residential locations, starting from the collection, storage and transportation process, the waste sorting process and the waste recycling process. The results of this research are, First; Waste management in the Forestry Vocational School Housing Complex and Perum Kampung Dalam Lestari is in accordance with existing regulations, starting from the collection, container and transportation process, the waste sorting process and the waste recycling process. Second, there are still people managing waste at Perum Griya Cemara Asri who manage it independently, not using SNI standard containers, and there are still very few people who participate in sorting waste. Third, the waste management problems that are still encountered are: there are still illegal dumping near the research location, there are still residents who manage waste by burning it in the open field, there are still residents who have not separated the waste, there are still a few residents who are willing to become members of the Waste Bank and there are still people who who are not yet willing to pay waste fees